Bell pepper rootstocks with multiple resistance to soilborne diseases - Ragassi, Carlos Francisco; Silva da Costa Ribeiro, Cláudia; Patiño-Torres, Albania; Lopes, Carlos Alberto; Borges Pinheiro, Jadir; Reis, Ailton (Revista Ceres, 2022)
Grafting has been increasingly used to overcome soilborne pathogens. The commercial rootstock hybrids AF-8253 (Sakata) and Fortaleza (Takii), as well as Embrapa’s new hybrid, BRS Acará, were evaluated as rootstocks for the bell pepper hybrids Margarita (Syngenta) and Pampa (Clause) as scions, under natural infestation of Ralstonia pseudosolanacearum, as well as upon artificial inoculation with a) ten Ralstonia isolates, b) one Phytophthora capsici isolate, c) Meloidogyne incognita race 1, and d) Meloidogyne enterolobii (only rootstocks for c and d). Grafted bell peppers consistently showcased a higher productivity than did non-grafted ones under natural R. pseudosolanacearum infestation, and the rootstock genotype affected fruit size distribution. Rootstocks presented higher resistance than did commercial bell pepper hybrids (scions) for 6 out of 10 Ralstonia isolates. AF-8253 and BRS Acará displayed an immune-like response to P. capsici, while Fortaleza was moderately resistant (25% symptomatic plants) and the bell pepper hybrids (scions) were susceptible (100% symptomatic plants). Rootstocks were immune to M. incognita race 1, but slightly (AF-8253 and BRS Acará) or moderately (Fortaleza) resistant to M. enterolobii. Grafting with BRS Acará, as well as with AF-8253 or Fortaleza, is recommended for managing bacterial wilt, Phytophthora blight, and root-knot nematodes.